Business plan - bakery in Moscow - Toniaeva, Marina (2019)
The aim of my Bachelor Thesis is to create a business plan for the bakery “Malvina” in Moscow, which produce traditional products with the unique recipes. The purpose is to give a detailed description of the business and evaluate the Russian market, to implement the business plan in the real life.The thesis is divided into two main parts. The theoretical part describes methods and approaches that should be used in the business plan. The practical part of the thesis includes a description of the product and services, different analyses and researches of the Russian market. Furthermore, the marketing and financial plans were drawn up.